MEDIA PROMOSI MELALUI APLIKASI TIKTOK DALAM PRESFEKTIF ULAMA - Rukhmianti, Septiana Titin Dwi; Afwan, Arju; Hana, Kharis Fadlullah (LP2M and Shariah Faculty of The Pontianak State Institute of Islamic Studies, 2023)
This study aims to find out the opinion of NU and Muhammadiyah scholars regarding content and promotional media through the TikTok application. To find out the answer to this question, qualitative research was carried out with the type of phenomenological research using data collection through field research and some of the data was obtained through interviews and several valid sources and also some book literature. Researchers are also limited by time, place, and problems studied in the form of activity programs, individuals, and events. The subjects of this study were addressed to lecturers at IAIN Kudus, and several NU and Muhammadiyah scholars in Pati, such as Mr. Muhamat Nur Maarif, MH, Mr. H. Ahmad Lazim, Mr. KH. Ahmad Zuhri, Mr. KH Fuad, S.Pd, Mr. K. Anwar Hasim, Lc. Based on the results of this study, the authors conclude that TikTok is an application that provides unique and interesting special effects that users can use easily so they can make short videos with cool results that can be shown to friends or other users. Playing the TikTok application is legally permissible, as long as it doesn't contain disobedience, lust, and passion is not a problem. And the content in the TikTok application is positive and negative as explained by the informants, and most of the content is negative. Meanwhile, the development of promotional media using the TikTok application is developing so quickly and making it easier for online businesses, especially by making short videos of their merchandise. Promotion through the TikTok application is very effective and can be followed by other business people, especially beginners who want to start a business.